(untitled) (Emancipação, 2026)
The work of social workers has changed in tandem with the increasing use of information and communication technologies. The process of digitizing the Brazilian government, coupled with the administrative counter-reforms implemented by the government, aims to optimize service delivery, thereby enhancing the efficiency and effectiveness of public administration. In terms of social policies, the use of technologies as part of work processes is evident in the adoption of electronic medical records, as well as the systematization of information published in open-access databases hosted by various public agencies, allowing access to a wide range of information regarding the profile of the user population, the scope of services, and the location of the service network. This article aims to present the consequences of technology use in the work of social workers. To this end, a qualitative, exploratory study was conducted, beginning with a literature review and drawing on studies regarding work under capitalism and ICTs; access to databases; and the systematization of professional experiences. As a result, intensification takes various forms: in the delivery of social services, it becomes part of work processes; in the generation of data on the client population and the scope of service provision; and in access to real-time information through the use of digital platforms and tools. An extension of the workday and a narrowing of the gap between time spent working and time spent resting were observed among social workers.